2016
DOI: 10.1182/blood.v128.22.3345.3345
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Veto Cells for Non-Myeloablative Haploidentical HSCT: Combining Anti-Viral and Graft Facilitating Activity

Abstract: Transplantation of T cell-depleted BM (TDBM) under mild conditioning, associated with minimal toxicity and reduced risk of GVHD, offers an attractive therapeutic option for patients with nonmalignant hematologic disorders or can be used to induce immune tolerance to subsequent organ transplantation. However, overcoming TDBM rejection after reduced conditioning remains a challenge. We previously demonstrated that this barrier can be overcome using donor-derived naïve CD8 T cells if they are expanded against thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Results showed that Tcm grown from a starting population of CD8 + CD44 + cells were also able to achieve marked donor chimerism when administered with megadose TCD allogeneic HSCT in sublethally irradiated Balb/c recipients. Notably, infusion of 5 × 10 6 Tcm into sublethally irradiated mice (5.5 Gy TBI) without BMT did not cause any GVHD, as measured by weight loss, in contrast to the CD8 + CD44 + T cells used to generate the Tcm [43].…”
Section: Biology Of Transplantationmentioning
confidence: 91%
See 3 more Smart Citations
“…Results showed that Tcm grown from a starting population of CD8 + CD44 + cells were also able to achieve marked donor chimerism when administered with megadose TCD allogeneic HSCT in sublethally irradiated Balb/c recipients. Notably, infusion of 5 × 10 6 Tcm into sublethally irradiated mice (5.5 Gy TBI) without BMT did not cause any GVHD, as measured by weight loss, in contrast to the CD8 + CD44 + T cells used to generate the Tcm [43].…”
Section: Biology Of Transplantationmentioning
confidence: 91%
“…The resulting population was subjected to third-party stimulation by coculture with irradiated splenocytes generated from spleens of OVA-expressing mice under cytokine deprivation. HIL-15 (10 ng/mL) was added to the culture at 60 hours after culture initiation to induce the cells to express a Tcm-like phenotype, as described previously for anti-third-party Tcm generated from WT naïve CD8 + T cells (WT Tcm) [43].…”
Section: Biology Of Transplantationmentioning
confidence: 99%
See 2 more Smart Citations